Down-regulation of Fibulin-5 is associated with aortic dilation: role of inflammation and epigenetics. Issue 3 (18th April 2016) - Orriols, Mar; Varona, Saray; Martí-Pàmies, Ingrid; Galán, María; Guadall, Anna; Escudero, José Román; Martín-Ventura, José Luis; Camacho, Mercedes; Vila, Luis; Martínez-González, José; Rodríguez, Cristina
Abstract: Aims: Destructive remodelling of extracellular matrix (ECM) and inflammation lead to dilation and ultimately abdominal aortic aneurysm (AAA). Fibulin-5 (FBLN5) mediates cell–ECM interactions and elastic fibre assembly and is critical for ECM remodelling. We aimed to characterize FBLN5 regulation in human AAA and analyse the underlying mechanisms. Methods and results: FBLN5 expression was significantly decreased in human aneurysmatic aortas compared with healthy vessels. Local FBLN5 knockdown promoted aortic dilation and enhanced vascular expression of inflammatory markers in Ang II-infused C57BL/6J mice. Inflammatory stimuli down-regulated FBLN5 expression and transcriptional activity in human aortic vascular smooth muscle cells (VSMC). Further, aortic FBLN5 expression was reduced in LPS-challenged mice. A SOX response element was critical for FBLN5 promoter activity. The SOX9 expression pattern in human AAA parallels that of FBLN5, and like FBLN5, it was reduced in TNFα-stimulated VSMC. Interestingly, SOX9 over-expression prevented the cytokine-mediated reduction of FBLN5 expression and transcription. The inhibition of Class I histone deacetylases (HDACs) by MS-275 or gene silencing attenuated the inflammation-mediated decrease of FBLN5 expression in VSMC and in the vascular wall. Consistently, HDAC inhibition counteracted the reduction of SOX9 expression induced by inflammatory stimuli and prevented the TNFα-mediated decrease in the binding of SOX9 to FBLN5 promoter normalizing FBLN5 expression. Conclusion: We evidence the deregulation of FBLN5 in human AAA and identify a SOX9/HDAC-dependent mechanism involved in the down-regulation of FBLN5 by inflammation. HDAC inhibitors or pharmacological approaches that aimed to preserve FBLN5 could be useful to prevent the disorganization of ECM induced by inflammation in AAA.